Measuring the continuation of antidepressant exposure prior to, during, and after pregnancy: A scoping review protocol - Lauren S. Tailor; Hilary K. Brown; Jessie Cunningham; Simone N. Vigod; Erzsébet Horváth-Puhó; Sonia M. Grandi (PLoS ONE, 2025)
Objective The goal of this scoping review is to summarize how prior studies have measured antidepressant continuation/discontinuation prior to, during, and after pregnancy. Introduction Pregnant individuals and healthcare providers are faced with difficult decisions about whether to continue antidepressants in pregnancy due to the historical exclusion of pregnant women from clinical trials and the lack of rigorous evidence to support these decisions. Prior studies examining the effects of pre- and perinatal antidepressant use on perinatal outcomes using observational data have been inconsistent, primarily due to the binary (ever/never) categorization of exposure, which may not accurately reflect real-world use. Inclusion criteria The population for this review consists of pregnant individuals. The concept is the measurement of continued preconception, prenatal, and postpartum antidepressant use. We will include human studies (no restrictions on language or geographic location) with the following study designs: cohort studies, cross-sectional studies, case-control studies, and descriptive analyses or spontaneous reports that reference antidepressant use over time. Methods We will conduct a scoping review using the JBI (formerly Joanna Briggs Institute) manual for scoping reviews and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews Checklist (PRISMA-ScR). The search strategy will be performed using database-specific nomenclature in MEDLINE, EMBASE, PsycINFO, Cochrane, Web of Science, and Canada’s Drug Agency Grey Matters Guide for grey literature, limiting the final search to publications since 2022 to include contemporary data. Two independent reviewers will 1) screen titles/abstracts/full-texts and 2) extract data. Findings will summarize measurements of antidepressant continuation during the perinatal period, categorizing studies based on the descriptions of timing, duration, adherence, and exposure ascertainment. Conclusion This scoping review will establish the extent to which prior studies have been able to measure continued use to inform a clear definition of continued antidepressant exposure to be used in future studies. Review registration: Open Science Framework https://osf.io/2ewpq